Variations in habitat metrics along plantation chronosequences: Contrasting tree plantations in subtropical forest and grassland - Santoandre, Santiago (2021)
The increasing demand for raw materials favours habitat conversion into tree plantations in different biomes over the world. In Argentina, fast-growing plantations occur in physiognomically contrasting biomes, such as the subtropical forest and grassland. Our objectives were to analyze variations in basic habitat metrics and their similarity to the natural habitat along pine plantation cycles, and to compare those patterns between plantations developing in a subtropical forest and a grassland biome. In each biome we selected pine stands of eight ages to represent the environmental gradient of the forest cycle, and natural areas. At each site we estimated the temperature, thermal variability, relative humidity, and percentage coverage of herbaceous plants, shrubs and canopy. We explored environmental similarity between plantations and the natural habitat. In general, patterns of the environmental variables along plantation chronosequences were similar between plantations developing in different biomes. As expected, opposite patterns of similarity in most environmental variables between plantations and the natural habitat were observed along chronosequences developing in contrasting biomes. The time period of high environmental similarity between plantations and the natural environment was longer in the subtropical forest than in the grassland. Our results have implications for land use planning and biodiversity conservation.